The Impact of Integrated Multidisciplinary Palliative Care Program on Symptoms in Patients at the Palliative Care Ward—An Audit and a Protocol of Prospective Controlled Investigation. Issue 3 (July 2017) - Jülich, Andreas; Spreu, Thomas; Buchhold, Britta; Usichenko, Taras
An integrated multidisciplinary palliative care (IMPC) program is a promising tool to improve symptom control in patients at the end of life. The aim was to study the feasibility of the IMPC program in patients at the palliative care (PC) ward. A retrospective audit, using the extended Edmonton Symptom Assessment Scale (ESAS), was conducted on the PC ward of the university hospital. Consecutive patients who were admitted for the IMPC program during 1 year were considered. One hundred forty-eight cases (93% with underlying cancer) were analyzed. The intensity of pain levels, nausea, vomiting, shortness of breath, and sleep disorders decreased at least by 50% ( P < .0001) during the 13 (median) days of IMPC. Integrated multidisciplinary PC program was associated with symptom improvements in patients at the PC ward. The information generated supports sample size calculation for a prospective controlled trial.